Justiça e fraternidade: o mínimo existencial como concretizador do direito ao desenvolvimento - Tsuruda, Juliana Melo (2016)
This research paper aims to study the relationship between the right to the existential minimum and the right to development in order to understand the extent and effectiveness of both rights. Based on the study of poverty as a violation of human rights, this paper seeks to justify through the values of justice and fraternity here understood as solidarity the right to the minimum necessary to a dignified existence as a starting point towards the desired right to development. The topic in question is justified by the empirical data on poverty and underdevelopment to which human rights have proposed solutions throughout its history notably through an international treaty that established the International Labour Organization within the Nations League, the United Nations Charter and an entire normative body created when the renowned Universal Declaration of Human Rights was adopted in 1948. The right to the existential minimum, which within the scope of fundamental rights finds some reductionist views that border on a lack of regard for human dignity, as a human right emerges as the true path to the realization of the right to development thanks to the wide recognition of economic, social and cultural rights as a mandatory bond that engages the State and society in their duties of respecting, protecting and ensuring the rights of people living in poverty. Last but not least, the right to development is revealed as the only possible tool to the solution of social issues seen by the Christian social doctrine as the conflict between labor and capital which generates new forms of social exclusion. Development, translated as a movement towards betterment, is presented as the right of peoples to the full enjoyment of human rights for every person and every society, a true expression of the common good